2008
DOI: 10.1186/1476-7961-6-3
|View full text |Cite
|
Sign up to set email alerts
|

Incense smoke: clinical, structural and molecular effects on airway disease

Abstract: In Asian countries where the Buddhism and Taoism are mainstream religions, incense burning is a daily practice. A typical composition of stick incense consists of 21% (by weight) of herbal and wood powder, 35% of fragrance material, 11% of adhesive powder, and 33% of bamboo stick. Incense smoke (fumes) contains particulate matter (PM), gas products and many organic compounds. On average, incense burning produces particulates greater than 45 mg/g burned as compared to 10 mg/ g burned for cigarettes. The gas pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
171
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(174 citation statements)
references
References 65 publications
(55 reference statements)
0
171
2
1
Order By: Relevance
“…In this study, the PM is generated by burning incense. The burning incense contains PM above 45 mg g À 1 burned, and the exhaust smoke contains a variety of pollutant gases, including CO, CO 2 , NO 2 , SO 2 and also volatile organic compounds, such as benzene, toluene, xylenes, aldehydes and polycyclic aromatic hydrocarbons 28 . This complex air exhaust is a model system containing many of the components present in polluted air during hazy days.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the PM is generated by burning incense. The burning incense contains PM above 45 mg g À 1 burned, and the exhaust smoke contains a variety of pollutant gases, including CO, CO 2 , NO 2 , SO 2 and also volatile organic compounds, such as benzene, toluene, xylenes, aldehydes and polycyclic aromatic hydrocarbons 28 . This complex air exhaust is a model system containing many of the components present in polluted air during hazy days.…”
Section: Resultsmentioning
confidence: 99%
“…However, incense burning has been considered as a noteworthy source of indoor air pollution. Fine and ultrafine particulate matter, volatile organic compounds, other gaseous compounds, and heavy metals are emitted from incense burning 9, 10, 11, 12. For children, exposure to incense smoke has been associated with increased respiratory symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Secondarily, fine particles are created when chemicals react in the atmosphere and grow through particle-particle or gas-particle interactions. PM 2.5 is believed to pose the greatest health risks because they can go as deep as the alveoli [2]. However, Fierro [1] reported that PM 2.5 was associated with a 36 % increase in deaths from lung cancer and 26% increase in cardiopulmonary deaths and these risks are even greater for people over the age of 65.…”
Section: Introductionmentioning
confidence: 99%